Characteristics of lead-free transparent dielectrics contaminated with moisture - Oh, Young-Jei; Jang, Byung-Koog; Kim, Hyun-Oh; Lim, Dae-Soon (ELSEVIER SCIENCE SA, 2011)
A green sheet of lead-free transparent dielectrics for the upper panel in a plasma display panel (PDP) was prepared by the tape-casting method. The dispersion characteristics of dielectric frit powder contaminated with moisture of 0-0.1 wt% were investigated to evaluate the properties of the fired transparent dielectric films. The dispersion stability was not severely affected by moisture up to 0.1 wt% on the frit powder, but agglomerations, together with precipitation of the powders, occurred under all conditions of moisture contamination. Moisture affects the pore size and distribution of the fired transparent dielectric thin films, which reduces the strength of the green sheet and withstanding voltage of the films fired. (C) 2011 Elsevier BM. All rights reserved.
Keywords: TAPE-CASTING TECHNOLOGY; SLIP ADDITIVES; SOLVENTS